Rancang Bangun Monitoring Suhu dan Kelembaban Menggunakan Sensor DHT 22 Berbasis Web Server Dengan Media Transmisi LoRa di Shelter Navigasi DVOR - Siallagan, Wendi; Suhendra, Tonny; Hekso Yunianto, Anton (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2023)
Abstract— DVOR (Doppler VHF Omnidirectional Range) equipment is very sensitive to room temperature. If the temperature is not between 18 °C to 24 °C then the DVOR Navigation device can be extinguished. The purpose of this study was to design a DVOR Navigation shelter temperature and humidity monitor using LoRa (Long Range) delivery and displayed in a web server. The study used a DHT 22 as temperature sensor, RTC DS 3231 to retrieve time data, a Micro SD Card module used to store data, LoRa as a data transmission medium, and ESP32 as a microcontroller. The study successfully designed and developed a temperature monitoring instrument using the DHT 22 sensor. The device is capable of measuring temperature and being sent according to delivery time as well as storing data to the SD Card via LoRa and displayed in the form of a web server. The results of observations showed that data transmission must be no obstacle or LOS (Line of Sight) in order to get good data.